PEMANFAATAN KONJUNGSI SUBORDINATIF DALAM TEKS MOTIVASI DI MEDIA SOSIAL INSTAGRAM - Setyawati, Nanik; Prayogi, Icuk; Indrariani, Eva Ardiana; Kurniawan, Latif Anshori (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2024)
Good knowledge and understanding of conjunctions, especially subordinating conjunctions, will help language users communicate effectively. In this research, the relationship between meaning and subordinating conjunction markers in motivational texts on Instagram social media will be explored through a qualitative approach. Data collection was carried out by observing the use of subordinating conjunctions in motivational texts on social media from four accounts on Instagram. To find out the meaning relationship contained in subordinating conjunctions, the researcher carried out data analysis using the matching method; Meanwhile, to find out the markers for subordinating conjunctions, the data was analyzed using the agih method. Data that has been successfully analyzed is presented informally. The results obtained are that there are ten relationships in the meaning of subordinating conjunctions and their markers, namely: (1) relationships in the meaning of time, including: the beginning of the event marked since; the beginning of the time of an event marked by another event marked by, when, and while; the beginning of an event that is preceded by another event marked after; and the duration of an event marked with a certain event marked until; (2) the meaning relationship of terms marked as long as, if, if, if, and if; (3) the relationship between meaning and goal marked in order; (4) concessive meaning relationships marked although and although; (5) the meaning relationship between marked comparisons such as; (6) the meaning relationship of comparison is marked rather than;  (7) causal meaning relationship marked because; (8) the meaning relationship of the results marked then, until, and so; (9) the relationship between the meaning of marked tools with and without; and (10) the meaning relationship of complementation is marked by that. Pengetahuan dan pemahaman yang baik tentang konjungsi, khususnya konjungsi subordinatif akan membantu para pemakai  bahasa dalam berkomunikasi secara efektif. Dalam penelitian ini akan dieksplorasi seputar hubungan makna dan penanda konjungsi subordinatif dalam teks motivasi di media sosial Instagram melalui pendekatan kualitatif. Pengumpulan data dilakukan melalui penyimakan terhadap pemanfaatan konjungsi subordinatif dalam teks motivasi di media sosial dari empat akun di Instagram. Untuk mengetahui hubungan makna yang terdapat dalam konjungsi subordinatif, analisis data peneliti lakukan dengan metode padan; sedangkan untuk mengetahui penanda konjungsi subordinatif, data dianalisis dengan  memanfaatkan metode agih. Data yang telah berhasil dianalisis disajikan secara informal. Hasil yang diperoleh adalah adanya sepuluh hubungan makna konjungsi subordinatif dan penandanya, yaitu: (1) hubungan makna waktu, meliputi: awal peristiwa berpenanda sejak; awal waktu peristiwa yang ditandai dengan peristiwa lain berpenanda demi, ketika, dan selagi; awal suatu peristiwa yang didahului dengan peristiwa lain berpenanda setelah; dan lamanya suatu peristiwa yang ditandai dengan peristiwa tertentu berpenanda hingga; (2) hubungan makna syarat berpenanda asalkan, bila, apabila, jika, dan kalau; (3) hubungan makna tujuan berpenanda agar; (4) hubungan makna konsesif berpenanda walau dan meski; (5) hubungan makna pembandingan berpenanda seperti; (6) hubungan makna  perbandingan berpenanda daripada;  (7) hubungan makna sebab  berpenanda karena; (8) hubungan makna hasil berpenanda maka, sampai, dan sehingga; (9) hubungan makna alat berpenanda dengan dan tanpa; dan (10) hubungan makna komplementasi berpenanda bahwa.